The Implementation Of Linear Programming Simplex Method To Generate Optimal Profits An-Nisa Koya - Annisa Fitriyani; Suci Putri Lestari; Depy Muhamad Pauzy (Jurnal Fokus Manajemen, 2022)
This research aims to find out the profit optimization model in AN-NISA Koya company by using linear programming method simplex whether there is a difference between before and after using linear programming simplex method. The main raw materials used by the company are rice and granulated sugar. The study used interview data collection techniques, library studies, and observations. The method used in this study is a qualitative descriptive approach. The method used in this study is the linear programming simplex method which is calculated manually and with the help of POM-QM software. Based on the results of research, it is known that with the linear programming simplex method using the helped of POM-QM software the company can optimize profits. And from comparative analysis, there is a difference between the results of data before using linear programming method simplex and after using linear programming method simplex.